Yelick Receives ACM/IEEE Award. (Communications of the ACM, 2016)
The article announces the computer scientist Katherine Yelick has been granted the 2015 Association for Computing Machinery (ACM)/Institute of Electrical and Electronics Engineers (IEEE) Computer Society Ken Kennedy Award for her research on parallel computing environments.